Community Currencies, Exchange and Gift Economies in Latin America - Heras Monner Sans, Ana Ines (2014)
This essay portrays the key concepts around community currencies and discusses the relationship between such currencies and the framework of otra economía. Additionally, I present a short review of central ideas informing these issues from an anthropologically oriented perspective.